2006
DOI: 10.1094/cc-83-0569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amylose, Corn Protein, and Corn Fiber Contents on Production of Ethanol from Starch‐Rich Media

Abstract: Cereal Chem. 83(5):569-575The effects of amylose, protein, and fiber contents on ethanol yields were evaluated using artificially formulated media made from commercial corn starches with different contents of amylose, corn protein, and corn fiber, as well as media made from different cereal sources including corn, sorghum, and wheat with different amylose contents. Second-order response-surface regression models were used to study the effects and interactions of amylose, protein, and fiber contents on ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 42 publications
4
105
0
3
Order By: Relevance
“…Protein and oil values of landraces thus would appear to be higher than those reported for Corn Belt hybrids in multiple studies (Watson, 2003;Belyea et al, 2004;Dudley et al, 2007;Jaradat and Goldstein, 2013) and quality protein maize hybrids (Zarkadas et al, 2000). The crude fiber and ash content were reported to be lower in blue maize compared to yellow dent maize (Wu et al, 2006). In comparison with blue maize, commercial hybrids and modern varieties were reported to be higher in starch (Ridley et al, 2002;Scott and Blanco, 2009), which is consistent with the intense selection for higher grain yield in commercial hybrids.…”
Section: Accessionmentioning
confidence: 73%
“…Protein and oil values of landraces thus would appear to be higher than those reported for Corn Belt hybrids in multiple studies (Watson, 2003;Belyea et al, 2004;Dudley et al, 2007;Jaradat and Goldstein, 2013) and quality protein maize hybrids (Zarkadas et al, 2000). The crude fiber and ash content were reported to be lower in blue maize compared to yellow dent maize (Wu et al, 2006). In comparison with blue maize, commercial hybrids and modern varieties were reported to be higher in starch (Ridley et al, 2002;Scott and Blanco, 2009), which is consistent with the intense selection for higher grain yield in commercial hybrids.…”
Section: Accessionmentioning
confidence: 73%
“…The presence of ash and lipids negatively affects the utilization of sugar, which consequently influences the fermentation efficiency of different feedstocks (Wu et al 2006). These compounds appear to be important in determining the pH (positive correlation between pH and lipid contents) and conductivity of ethanol (positive correlations between ash and conductivity), thus having an impact on yeast growth regimes in the fermentation broth (Klinke et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [112], observed higher eYciency of ethanol production from waxy wheat as compared to that of normal wheat, corn of various amylose contents, and waxy and non-waxy sorghum.…”
Section: Wheatmentioning
confidence: 99%